Na stopě velkým savcům Šumavy - telemetrický projekt monitorující život kopytníků a šelem - Šustr, Pavel
The Šumava Mts. and the neighbouring Bavarian Forest belong to the last areas in Central Europe, where large herbivorous mammals (Red Deer - Cervus elaphus, Roe Deer - Capreolus capreolus and European Moose - Alces alces) can find enough space for their food requirements and can coexist with their predator (Lynx - Lynx lynx). The activities and results of research project aimed at environmental issues related to these species using the up-to-date technologies (GPS telemetry, phototraps) are presented. Pavel Šustr.